Pengaruh informasi berlebihan terhadap rasa lelah dan disorientasi dengan kognisi sebagai variabel moderasi dalam konten video - Kenny Kenny (MBR (Management and Business Review), 2020)
The purpose of this study is to analyze the effects of information overload on fatigue and disorientation with cognition as the mediator. The object of the study is Kwib, which is a company that engages in video making and animation. This study was conducted at people who use social media, specifically the ones who use social media with the feature of watching video content. In total 68 respondents have participated in this study. The results of this study show that while cognition is an effective mediator of fatigue, information overload does not have any effect on fatigue. However, another result of this study has also shown that when fatigue does occur for the respondent, it will lead to disorientation